Recent advances on surface enhanced Raman spectroscopy in safety assessment and quality control of meat and meat products - Meihong Wu; Hui He (Food Materials Research, 2024)
With the continuous development of spectroscopy technology, surface enhanced Raman spectroscopy (SERS) has been widely used as a fast and sensitive analysis method for the qualitative and quantitative analysis of trace analytes in foods. At present, SERS has been widely used in various fields such as food safety, materials, and biomedicine. However, the advances of SERS in meat safety and quality detection have not been summarized. In this review, the development history and detection principles of SERS are introduced and the advantages and potential of SERS application in the field of meat safety and quality detection evaluated. Then, two classical SERS detection modes were compared, namely labeled detection and label-free detection, in terms of the advantages, disadvantages, and application scopes. Furthermore, the specific applications of SERS in detecting bacteria, viruses, veterinary drug residues, food additives, illegal additives, and biotoxins in meat and meat products were presented. In addition, the development of SERS in meat adulteration and freshness identification are summarized. The prospects of the future development of SERS in meat safety and quality assessment will likely involve multiple method integrations, new material development, and artificial intelligence. It is expected that this review will not only provide a comprehensive summary and exploration of SERS in meat safety and quality assessment but also shed light on the future innovation and continued development of SERS in the food and meat industry.